Public use of external defibrillator in Hangzhou of China - Sheng, Jin Xiao; Kan, Ye; Gai, Zhang; Hao, Zhang (Asian Journal of Medical Sciences, 2021)
Background: Ventricular fibrillation (VF) is one of the causes of out-of-hospital cardiac arrest (OHCA). The increase in survival after out-of-hospital cardiac arrest is closely related to early detection and shortening the first defibrillation time. The implementation of AEDs deployment plan in public places in Hangzhou City provides an opportunity to improve the survival rate after out-of-hospital cardiac arrest, and the benefits and potentials are enormous. Aims and Objective: Placing AEDs in public areas can effectively treat patients with pre-hospital cardiac arrest, by evaluating the configuration and usage of public AEDs in Hangzhou during the past five years, to provide the basis for improving the public areas’ configuration AEDs network layout and related training management. Materials and Methods: The number of AEDs in public areas, the use of AEDs and the treatment effect in Hangzhou city from 2015 to 2020 were collected. Results: The number of AEDs in public areas, the use of AEDs and the treatment effect in Hangzhou city from 2015 to 2020 were collected. In 5 years, a total of 1201 AEDs were configured, Placed in densely populated areas such as transportation hubs, schools, and scenic spots as the main locations. 32 patients suffered prehospital cardiac arrest and used AEDs, the average age of the patients was 40.56 ± 17.20, and the ratio of male to female was 3.57:1, In 26 cases, the initial heart rhythm was ventricular fibrillation and defibrillation, Before the first aid personnel arrived, the first witnesses Implement rescue, 22 patients with ventricular fibrillation were resuscitated successfully, 10 cases failed to ROSC. In 6 patients with suspected cardiac arrest, there was no electric shock defibrillation, and the device correctly indicates that the problem is not caused by ventricular fibrillation, In 4 cases, there was no defibrillating rhythm. Conclusion: AEDs in public areas are effectively used to assist in the treatment of patients with cardiac arrest; It can increase the rate of main circulation recovery. We will further increase the number of AEDs in public places, promote first aid training programs for non-professionals, Improving the public health emergency network system is essential to improve the prognosis of patients with cardiac arrest.